And... where are the children?... the other aspect of femicide - Huaroc Llaja, Percy (2013)
Brief analysis and debate on Article 108 - B of the Peruvian Criminal Code, which establishes the basic and aggravated criminal forms of Femicide. In turn, the paper discusses the positive discrimination resultingfrom this offense regarding an equally vulnerable group, as are the children, who deserve equal protection by the Peruvian government.